2008
DOI: 10.1590/s1516-89132008000500007
|View full text |Cite
|
Sign up to set email alerts
|

Detection of GBV-C/HGV RNA in cervico-vaginal smears from healthy individuals

Abstract: The purpose of the present study was to evaluate the sexual transmission of GBV-C/HGV, through RNA detection in cervicovaginal smears. Therefore the GBV-C/HGV RNA in cervicovaginal smears from apparently healthy women was investigated using routine proceedings for prophylactic screening to cervical cancer. GBV-C/HGV RNA was detected by reverse transcriptase and polymerase chain reaction (RT-PCR). Only one woman presented co-infection with human papilloma virus (HPV). The GBV-C/HGV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…A study performed in Brazil supports the importance of condoms for preventing sexual transmission of HPgV . Cervicovaginal smears were collected from 73 healthy women who had undergone routine screening for cervical cancer; a high prevalence of HPgV (17.6%) was found in the genital mucosa of this population .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A study performed in Brazil supports the importance of condoms for preventing sexual transmission of HPgV . Cervicovaginal smears were collected from 73 healthy women who had undergone routine screening for cervical cancer; a high prevalence of HPgV (17.6%) was found in the genital mucosa of this population .…”
Section: Discussionmentioning
confidence: 87%
“…22,23 A study performed in Brazil supports the importance of condoms for preventing sexual transmission of HPgV. 24 Cervicovaginal smears were collected from 73 healthy women who had undergone routine screening for cervical cancer; a high prevalence of HPgV (17.6%) was found in the genital mucosa of this population. 24 Serum extravasation could not be ruled out by the researchers as no blood samples were tested; however, the high prevalence reported suggested that the genital mucosa was the first line of defense for sexually transmitted infections.…”
Section: Discussionmentioning
confidence: 98%